How does your doctor talk with you?: Preliminary validation of a brief patient self-report questionnaire on the quality of physician-patient interaction - Bieber, Christiane; Müller, Knut G.; Nicolai, Jennifer; Hartmann, Mechthild; Eich, Wolfgang (Journal of clinical psychology in medical settings, 2010)
The quality of physician-patient interaction is increasingly being recognized as an essential component of effective treatment. The present article reports on the development and validation of a brief patient self-report questionnaire (QQPPI) that assesses the quality of physician-patient interactions. Data were gathered from 147 patients and 19 physicians immediately after consultations in a tertiary care outpatient setting. The QQPPI displayed good psychometric properties, with high internal consistency and good item characteristics. The QQPPI total score showed variability between different physicians and was independent of patients’ gender, age, and education. The QQPPI featured high correlations with other quality-related measures and was not influenced by social desirability, or patients’ clinical characteristics. The QQPPI is a brief patient self-report questionnaire that allows assessment of the quality of physician-patient interactions during routine ambulatory care. It can also be used to evaluate physician communication training programs or for educational purposes.
Gesehen am 01.02.2023